Case studies in forensic anthropology : bonified skeletons - Garvin, Heather M.; Langley, Natalie R. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
'Through a set of unique cases presented by a diverse international group of practicing forensic anthropologists, Case Studies in Forensic Anthropology seeks to prepare students and professionals for future cases they may confront'
Includes bibliographical references and index.
Keywords: Forensic anthropology -- Case studies; Forensic osteology -- Case studies; Human remains (Archaeology) -- Case studies